Daptomycin in treatment of Gram-positive infections in children with hematological disorders - Z. M. Dyshlevaya; A. N. Arkhipova; Yu. V. Pashko; L. V. Guk; E. V. Skorobogatova; G. P. Pavlova; A. A. Bologov (Вопросы современной педиатрии, 2012)
The study of efficacy and toxicity of daptoycin in treatment of Gram-positive infectons n children with hematological disorders wasperformed. Twelve patients (4 girls and 8 boys) with signs of Gram-positive infections were examined. Staphylococcus aureus wasfound in 66,6% (8 patients), among them in 3 patients strains were methicillin-resistant; Staphylococcus epidermidis — was found in 16,6% (2 patients); Enterococcus faecalis — in 16,6% (2 patients). By the time of development of infectious complications 7 patients (58,3%) have received antibiotic treatment, in 5 other patients daptomycin was the first-line antibacterial drug. The mean dosage of the drug was 5,8 mg/kg/day. In order to reveal the drug toxicity the monitoring of biochemical serum markers (fibrinogen, ALT, AST, LDG, CPK, creatinine) was performed. The complete resolution of infectious complications occurred in 12,1 ± 4,3 days. The mean duration of daptomycin treatment was 14,2 ± 3,2 days. During the treatment reliable lower of fibrinogen (6,4 ± 1,1 g/l and 3,1 ± 0,9 g/l, р = 0,05) and c-reactive protein (CRP) (12,5 ± 7,1 mg/dL and 3,4 ± 1,8 mg/dL, р = 0,04) was observed. No side effects were observed in all the patients. The performed study allowed to make a conclusion, that daptomycin is an effective and safe drug in treatment of Grampositive infections in children with hematological disorders even with concomitant hypogranulocytosis.Key words: daptomycin, Gram-positive infections, onco-hematology.